2015
DOI: 10.3390/e17117584
|View full text |Cite
|
Sign up to set email alerts
|

Choice Overload and Height Ranking of Menus in Partially-Ordered Sets

Abstract: When agents face incomplete information and their knowledge about the objects of choice is vague and imprecise, they tend to consider fewer choices and to process a smaller portion of the available information regarding their choices. This phenomenon is well-known as choice overload and is strictly related to the existence of a considerable amount of option-pairs that are not easily comparable. Thus, we use a finite partially-ordered set (poset) to model the subset of easily-comparable pairs within a set of op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
2
1
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…[35]. Indeed, it is advisable to avoid assigning fewer subjective evaluation tasks to mitigate cognitive errors [4,64] As suggested by Axiom 1, the τx similarity between two incomplete rankings can be equivalently calculated by simply dropping the alternatives unranked by either ranking (i.e., by projecting them to the subset of objects evaluated by both). While this may seem to remove the incomplete data from the researcher's view when comparing two incomplete rankings, we emphasize that the consensus ranking problem (see (1) or ( 2)) involves accruing the comparisons between the candidate solution (always a complete ranking) and each input ranking (which may be incomplete or complete).…”
Section: Derivation Of New Correlation Coefficient and Its Axiomatic ...mentioning
confidence: 99%
“…[35]. Indeed, it is advisable to avoid assigning fewer subjective evaluation tasks to mitigate cognitive errors [4,64] As suggested by Axiom 1, the τx similarity between two incomplete rankings can be equivalently calculated by simply dropping the alternatives unranked by either ranking (i.e., by projecting them to the subset of objects evaluated by both). While this may seem to remove the incomplete data from the researcher's view when comparing two incomplete rankings, we emphasize that the consensus ranking problem (see (1) or ( 2)) involves accruing the comparisons between the candidate solution (always a complete ranking) and each input ranking (which may be incomplete or complete).…”
Section: Derivation Of New Correlation Coefficient and Its Axiomatic ...mentioning
confidence: 99%
“…Research has attempted to identify the optimal number of options for consumers, and it has been found that a choice set between 8 and 15 options is preferred (Chernev et al, 2015; Sharma & Nair, 2017). Large choice sets may initially be appealing; however, if cognitive load is present, the motivation to make a selection is reduced (Basili & Vannucci, 2015). Studies conducted in the areas of charitable giving and travel souvenirs indicated that choice overload did not occur (Lindkvist & Luke, 2022; Sthapit, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Research has attempted to identify the optimal number of options for consumers, and it has been found that a choice set between 8-15 options is preferred (Chernev et al, 2015;Sharma & Nair, 2017). Large choice sets may initially be appealing, however, if cognitive load is present, the motivation to make a selection is reduced (Basili & Vannucci, 2015). Studies conducted in the areas of charitable giving and travel souvenirs indicated that choice overload did not occur (Lindkvist & Luke, 2022;Sthapit, 2018).…”
Section: Introductionmentioning
confidence: 99%